PENGARUH METODE READING GUIDE TERHADAP KEMAMPUAN MEMAHAMI ISI BACAAN PADA SISWA KELAS V SD NEGERI SUKADAMAI - Desi Oktarina Oktarina; Hetilaniar Hetilaniar Hetilaniar; Aldora Pratama Pratama (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
This research aims to determine the effect of the reading guide method on the ability to understand reading content in fifth grade students at Sukadam State Elementary School. This type of research is experimental quantitative research using the Pre-Experimental Design method with a One Group Pretest-Posttest Design research design. The population in this study were fifth grade students at Sukadam State Elementary School with a sample of grade V as the experimental class who were treated using the reading guide method with a sample selection technique, namely total sampling. Data collection techniques are carried out using observation, documentation and tests. By analyzing the data using the Paired Sample t Test with the help of SPSS version 23. The results of the research show that there is an influence of the reading guide method on the ability to understand reading content in fifth grade students at Sukadam State Elementary School. In the Paired Sample t Test, the Sig (2-tailed) value was 0.000 < 0.05. Thus, it can be concluded that there is a significant influence of the use of the reading guide method on the ability to understand reading content in fifth grade students at Sukadam State Elementary School.Keywords: Reading Guide Method, Ability to understand the content of the reading.